Pemberdayaan Masyarakat dalam Upaya Meminimalisir Asap Pabrik Menggunakan Teknik Penanaman Kokedama Tanaman Sansevieria di Wilayah Dusun Jetak Desa Sindangsari - Devina Dzahraini; Dita Destiasti; Aisya Rahmawaty; Adhynda Maulyna Duta Mahardyka; Salma Hazar Azzahra; Thallia Salfamaura Putri Sahdan; Putri Salma Andina; Muhammad Zahran; Andy Muharry (Lembaga Pengembangan Kinerja Dosen, 2024)
Air pollution is not an unfamiliar phenomenon for areas surrounding industries. The Cikoneng area has a wok industry center where the production process produces air pollution fumes. The wok industry center is adjacent to residential houses so that the factory smoke produced has an impact on the health of the surrounding community. Therefore, the targets of counseling are community leaders, health cadres, youth organizations, and residents who live around the industrial area. The purpose of this empowerment activity is to increase community knowledge, awareness, and creativity towards planting Sansevieria plants with the kokedama technique to maintain environmental health around the wok industry. The material was given using the lecture method with the help of power point media and leaflets. While the practice of planting Sansevieria with kokedama technique uses lecture and simulation methods. The Wilcoxon test was used to measure the level of knowledge of participants from the pre-test and post-test results which could show a difference in results before and after providing material with asymp. Sig (2-tailed) of 0.002, it can be concluded that there is an increase in knowledge in participants who take part in counseling activities. It is hoped that the people of Jetak Hamlet can minimize air pollution generated from the wok industry process by planting Sansevieria plants.